Treatment of Primary Aldosteronism and Reversal of Renin Suppression Improves Left Ventricular Systolic Function - Puar, Troy H.; Cheong, Chin Kai; Foo, Roger S.Y.; Saffari, Seyed Ehsan; Tu, Tian Ming; Chee, Min Ru; Zhang, Meifen; Ng, Keng Sin; Wong, Kang Min; Wong, Andrew; Ng, Foo Cheong; Aw, Tar Choon; et al. (Frontiers in Endocrinology, 2022)
Introduction Primary aldosteronism (PA) is associated with increased risk of cardiovascular events. However, treatment of PA has not been shown to improve left ventricular systolic function using the conventional assessment with left ventricular ejection fraction (LVEF). We aim to use speckle–tracking echocardiography to assess for improvement in subclinical systolic function after treatment of PA. Methods We prospectively recruited 57 patients with PA, who underwent 24–hour ambulatory blood pressure (BP) measurements and echocardiography, including global longitudinal strain (GLS) assessment of left ventricle, at baseline and 12 months post–treatment. Results At baseline, GLS was low in 14 of 50 (28.0%) patients. On multivariable analysis, GLS was associated with diastolic BP (P=0.038) and glomerular filtration rate (P=0.026). GLS improved post–surgery by –2.3, 95% CI: –3.9 to –0.6, P=0.010, and post–medications by –1.3, 95% CI: –2.6 to 0.03, P=0.089, while there were no changes in LVEF in either group. Improvement in GLS was independently correlated with baseline GLS (P<0.001) and increase in plasma renin activity (P=0.007). Patients with post–treatment plasma renin activity ≥1ng/ml/hr had improvements in GLS (P=0.0019), while patients with persistently suppressed renin had no improvement. Post–adrenalectomy, there were also improvements in left ventricular mass index (P=0.012), left atrial volume index (P=0.002) and mitral E/e’ (P=0.006), while it was not statistically significant in patients treated with medications. Conclusion Treatment of hyperaldosteronism is effective in improving subclinical left ventricular systolic dysfunction. Elevation of renin levels after treatment, which reflects adequate reversal of sodium overload state, is associated with better systolic function after treatment.